Answer:
<u>m</u><u> </u><u>is</u><u> </u><u>√</u><u>2</u>
Step-by-step explanation:
![{ \tt{ \sqrt{150} - \sqrt{12}m + \sqrt{54} = 0 }} \\ { \tt{ \sqrt{12}m } = \sqrt{150} - \sqrt{54} } \\ { \tt{ (\sqrt{4 \times 3}) m = ( \sqrt{25 \times 6} ) - ( \sqrt{9 \times 6}) }} \\ { \tt{( \sqrt{4 \times 3} )m = 5 \sqrt{6} - 3 \sqrt{6} }} \\ { \tt{2 \sqrt{3}m = 5 \sqrt{6} - 3 \sqrt{6} }} \\ { \tt{2 \sqrt{3} m = 2 \sqrt{6} }} \\ { \tt{ \sqrt{3} m = \sqrt{6} }} \\ { \tt{ \sqrt{3} m = ( \sqrt{3} \times \sqrt{2} ) }} \\ { \tt{m = \sqrt{2} }}](https://tex.z-dn.net/?f=%7B%20%5Ctt%7B%20%5Csqrt%7B150%7D%20%20-%20%20%5Csqrt%7B12%7Dm%20%2B%20%20%5Csqrt%7B54%7D%20%20%3D%200%20%7D%7D%20%5C%5C%20%7B%20%5Ctt%7B%20%5Csqrt%7B12%7Dm%20%7D%20%3D%20%20%5Csqrt%7B150%7D%20%20-%20%20%5Csqrt%7B54%7D%20%7D%20%5C%5C%20%7B%20%5Ctt%7B%20%28%5Csqrt%7B4%20%5Ctimes%203%7D%29%20m%20%3D%20%28%20%5Csqrt%7B25%20%5Ctimes%206%7D%20%29%20-%20%28%20%5Csqrt%7B9%20%5Ctimes%206%7D%29%20%7D%7D%20%5C%5C%20%7B%20%5Ctt%7B%28%20%5Csqrt%7B4%20%5Ctimes%203%7D%20%29m%20%3D%205%20%5Csqrt%7B6%7D%20%20-%203%20%5Csqrt%7B6%7D%20%7D%7D%20%5C%5C%20%7B%20%5Ctt%7B2%20%5Csqrt%7B3%7Dm%20%3D%205%20%5Csqrt%7B6%7D%20%20%20-%203%20%5Csqrt%7B6%7D%20%7D%7D%20%5C%5C%20%7B%20%5Ctt%7B2%20%5Csqrt%7B3%7D%20m%20%3D%202%20%5Csqrt%7B6%7D%20%7D%7D%20%5C%5C%20%7B%20%5Ctt%7B%20%5Csqrt%7B3%7D%20%20m%20%3D%20%20%5Csqrt%7B6%7D%20%7D%7D%20%5C%5C%20%7B%20%5Ctt%7B%20%5Csqrt%7B3%7D%20m%20%3D%20%28%20%5Csqrt%7B3%7D%20%5Ctimes%20%20%5Csqrt%7B2%7D%20%29%20%7D%7D%20%5C%5C%20%7B%20%5Ctt%7Bm%20%3D%20%20%5Csqrt%7B2%7D%20%7D%7D)
Answer:
![\frac{1}{5^{7}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B5%5E%7B7%7D%7D)
Step-by-step explanation:
![\frac{5^{-4}}{5^{3}} = \frac{1}{5^{7}}](https://tex.z-dn.net/?f=%5Cfrac%7B5%5E%7B-4%7D%7D%7B5%5E%7B3%7D%7D%20%3D%20%5Cfrac%7B1%7D%7B5%5E%7B7%7D%7D)
Avarage speed is (60+30)/2 = 45 miles per hour
bot is the same , Do not think so it is a right question.
Answer:
7 and 6 respectively
Step-by-step explanation:
Firstly, we have to solve the equations simultaneously.
2x + 7p = 56
3x - 11p = -45
Multiply equation I by 3 and ii by 2
6x +21p = 168
6x - 22p = -90
Subtract the second from first to yield:
43p = 258
p = 6
Insert this in equation 1 where we have 2x + 7p = 56
2x + 7(6) =56
2x + 42 = 56
2x = 14 and x = 7
The equilibrium price is 6 and the equilibrium quantity is 7